Long term stability of air processed inkjet infiltrated carbon-based printed perovskite solar cells under intense ultra-violet light soaking. Issue 10 (23rd February 2017) - Hashmi, Syed Ghufran; Tiihonen, Armi; Martineau, David; Ozkan, Merve; Vivo, Paola; Kaunisto, Kimmo; Ulla, Vainio; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract : The long term stability of air processed inkjet infiltrated carbon based perovskite solar cells (CPSCs) is investigated under intense ultra-violet light soaking equivalent to 1.5 Sun UV light illumination. Abstract : The long term stability of air processed inkjet infiltrated carbon based perovskite solar cells (CPSCs) is investigated under intense ultra-violet light soaking equivalent to 1.5 Sun UV light illumination. Two batches of the fabricated CPSCs were exposed systematically i.e. first without implementing any protective coating and then epoxying the CPSCs through a low cost commonly available epoxy which was applied to serve as a barrier against moisture and humidity intrusion. The CPSCs with no protective layer against moisture and humidity exhibited impressive preliminary stability for hundreds of hours during their exposure to intense UV light and provided great motivation to test the CPSCs further with more optimization. As a result, the CPSCs having commonly available epoxy as a protective barrier exhibited remarkable durability and showed no performance degradation for a period of 1002 hours under intense and continuous 1.5 Sun equivalent UV light illumination proving that the technology is clearly not inherently unstable and that future developments might lead to market breakthroughs.